Contaminant effects in shore crabs (Carcinus maenas) from Ria Formosa Lagoon - Maria, Vera L. (2020)
Defence and damage biomarkers signals were studied in female and male shore crabs Carcinus maenas transplanted between two sites at Ria Formosa Lagoon (South of Portugal). The cross transplantation occurred during 6 days at a hypothetical reference site (Ramalhete), and a contaminated site (Olhão). DNA unwinding technique was used for DNA integrity measurement. General enzymatic antioxidant responses in gills and hepatopancreas (catalase and gills glutathione peroxidase activities increase) showed that cross transplanted crabs (female and male) are suffering from pro-oxidant challenges at the Olhão site. Gills and hepatopancreas glutathione-S-transferase were reduced in both gender crabs transplanted from Ramalhete to Olhão. Metallothioneins induction occurred in crabs transplanted from Ramalhete to Olhão (contaminated by metals and polycyclic aromatic hydrocarbons (PAHs)). However metallothionein differences were also observed towards gender and organ specificities. High gills lipid peroxidation exist in male crabs transplanted from Ramalhete to Olhão, while in females it was the opposite. In both gender crabs from the Olhão site, gills DNA integrity decreased compared to the Ramalhete feral crabs. Moreover, hepatopancreas DNA integrity decreased in male crabs transplanted from Olhão to Ramalhete site which may be related to the environmental conditions (lower contamination levels) revealing the difficulty of selection of reference sites in field studies. Data demonstrated that female and male C. maenas antioxidant defences and damage biomarkers were sensitive to the mixture of contaminants present in these sites as well as good indicators of general stress.